2006
DOI: 10.1073/pnas.0510511103
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial transfer between cells can rescue aerobic respiration

Abstract: Current theory indicates that mitochondria were obtained 1.5 billion years ago from an ancient prokaryote. The mitochondria provided the capacity for aerobic respiration, the creation of the eukaryotic cell, and eventually complex multicellular organisms. Recent reports have found that mitochondria play essential roles in aging and determining lifespan. A variety of heritable and acquired diseases are linked to mitochondrial dysfunction. We report here that mitochondria are more dynamic than previously conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
784
1
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 886 publications
(815 citation statements)
references
References 27 publications
22
784
1
8
Order By: Relevance
“…In addition, it has been shown that the mitochondria can access thick nanotubes. Rescue of aerobic respiration in cells deficient in mitochondria was demonstrated by the intercellular transfer of whole mitochondria or mitochondrial DNA from normal cells, possibly involving membrane nanotubes formation (80). At present, the best datum for functional relevance of membrane nanotubules in immune-cell biology is the demonstration that they mediate communication of antigenic signals between myeloid cells (9,77).…”
Section: Membrane Nanotube Formationmentioning
confidence: 99%
“…In addition, it has been shown that the mitochondria can access thick nanotubes. Rescue of aerobic respiration in cells deficient in mitochondria was demonstrated by the intercellular transfer of whole mitochondria or mitochondrial DNA from normal cells, possibly involving membrane nanotubes formation (80). At present, the best datum for functional relevance of membrane nanotubules in immune-cell biology is the demonstration that they mediate communication of antigenic signals between myeloid cells (9,77).…”
Section: Membrane Nanotube Formationmentioning
confidence: 99%
“…In a report by Spees et al, active mitochondrial transfer occurred between adult stem cells and somatic cells, resulting in rescue of aerobic respiration in mammalian cells 11. Astrocytes were reported to shed mitochondria via membrane vesicles,7 which were then effectively transferred into neurons in response to cerebral ischemia, enhancing cell survival signaling 8.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs are readily obtained from a patient and rapidly expanded in culture so that it is feasible to administer very large numbers of autologous cells. After systemic infusion, the cells home to injured tissues and repair them by several different mechanisms, including differentiating into multiple cellular phenotypes, providing cytokines and chemokines (17), enhancing the proliferation of tissue-endogenous stem͞progenitor cells (18), and perhaps cell fusion (19) or transfer of mitochondria (20). In addition, MSCs suppress some immune reactions (21).…”
mentioning
confidence: 99%